SAT0042 Comparison between Two Clinical Pathways for the Management of Early Rheumatoid Arthritis: Routine Care versus Early Arthritis Clinic. (10th June 2014) - Farina, I.; Pignatti, F.; Galuppi, E.; Ciancio, G.; Govoni, M.
Abstract : Background: There is no doubt that the Early Arthritis Clinic (EAC) institution has provided a better awareness about early arthritis (EA) in term of potential evolution in Rheumatoid Arthritis (RA). However, to the best of our knowledge formal demostration that this organizational model has provided significant improvement in terms of pubblic health care and clinic outcomes is scant. Objectives: To evaluate whether or not significant differences in clinical and therapeutical outcomes exist between patients with RA managed in different organizational settings: routine care (RC) versus early arthritis clinic (EAC). Methods: Two groups of RA patients fulfilling 1987/ACR criteria attending our institution between 2002 and 2013 were retrospectively analyzed. In the first group RA diagnosis has been made between 2002 and 2008 and patients were followed by conventional approach (RC); in the second one RA diagnosis has been made between 2009 and 2013 but patients were followed within the EAC instituted since 2009 and ensuring rapid referral, tight monitoring and standardized therapeutic approach according to EULAR guidelines. Patients with available follow-up of at least 2 years were included. Lag time from symptoms onset to RA diagnosis and from symptoms onset to the beginning of DMARDs therapy were analyzed in the two groups. Clinical activity were also compared using DAS28 and EULAR response criteria at baseline (T0) and after 6 (T6), 12 (T12) and 24 (T24) months. The percentage of patients who started a biological therapy within 24 months were compared. Results: A total of 273 RA patients were evaluated: 209 (mean age 59±24.04 years, 165 F, 44 M) followed in RC and 64 (mean age 59±13.44 years, 50 F, 14 M) in EAC. Lag time from symptoms onset to diagnosis resulted significally lower (p<0, 0001) in patients managed in EAC (5.73±8.09 mesi) compared to that of the RC group (20.9±30.3 mesi) and treatment was started earlier in EAC population (7.17±8.26 mesi) than in RC (21.98±32.39 mesi) with a significant difference (p<0.0004). At baseline DAS28 evaluation was similar between groups (4.76±1.24 in RC vs 4.94±1.41 in EAC) and was significally reduced to 2.82±1.24 (RC) and 2.46±1.12 (EAC) after 24 months (p<0.036). A significant statistically difference emerged from the groups comparing mean ESR values (19.9±15.9 RC vs 13.6±11.3 EAC, p<0.003) and SJ (swollwn joints) value (1±1.8 RC vs 0.43±1.2 EAC, p<0.02) at T24. Within 24 months a biologic therapy was started in 29% of patients followed by RC, and in 9.3% in EAC group (p<0, 0013). Conclusions: In our experience the institution of an EAC clinical pathway provided an early diagnosis and early treatment and this time shortening translated into a better clinical outcomes and significant health care cost saving as regard to biologic drugs use. References: M. Govoni et al: Does early arthritis clinic oraganisation improve outcomes? What evidence is there? A systematic review. Clin Exp Rheumatol. 2013 May-Jun;31(3):443-51. Epub 2013 Feb 15. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.5466